Methodological aspects of software processes management of the airworthiness of aircraft - A. A. Itskovich; I. A. Faynburg; A. R. Aleksanyan (Научный вестник МГТУ ГА, 2016)
The article considers methodological aspects of software processes management of the airworthiness of the aircraft, solving problems of the formation and correction of flexible programs of the airworthiness of the aircrafts taking into ac-count the actual operating conditions and the technical condition of the airline fleet.